Pog - Haswell, Peter (New York : Orchard Books, 1989)
Relates, in simple text and illustrations, the adventures of an inquisitive pig names Pog.
"First published in Great Britain 1989 by Walker Books Ltd., London."
13 19 38 39
Keywords: Pigs -- Fiction